Rezension von: Midelfort, H. C. Erik, Witch Hunting in Southwestern Germany 1562-1684 - Stern, Bruno (Württembergisch Franken, 1979)
H.C. Erik Midelfort: Witch Hunting in Southwestern Germany 1562-1684. The social and intellectual foundations. (Hexenjagd in Südwestdeutschland. Die sozialen und intellektuellen Grundlagen). Stanford University Press / Stanford, California. 306 S., 15 Tabellen, 12 Abb.